Kepastian Hukum Dalam Pemungutan Retribusi Parkir Berdasarkan Peraturan Daerah Kota Binjai Nomor 04 Tahun 2011 Tentang Retribusi Jasa Umum - Dara Qurratu’ Aini Yusuf; Budiman Ginting; Sunarmi Sunarmi; Mirza Nasution (USU LAW JOURNAL, 2019)
Abstract. Regional retribution policy is implemented based on principles of democracy, equity, and justice, also on the role of society and accountability regarding regional potentials. The implementation of retribution collection for public service in regional government, particularly in Binjai Municipality, is based on the Regulations of Binjai Municipality No. 4/2011 on Retribution for Public Service. The results of the research demonstrate that the juridical regulations of the retribution collection for parking in Binjai is grounded on the Regional Government Regulations No. 4/2011 stating that it is collected based on the road class and vehicles parked at the public roadside. The higher the road class is and the more wheels the vehicles have, the higher the parking tariff is charged to the retribution payers for the parking service. The retribution collection for parking in Binjai is implemented in accordance with the Regional Government Regulations No. 4/2011 stipulating that the retribution collection for parking at public roadside is performed by parking management, either individually or by company who make a contract with the Technical Implementer of Parking Department as the parking management of Transportation Department in Binjai who gives mandates for parking. The policy issued by Binjai Municipality to overcome the obstacles in determining annual parking target which is too high and unrealistic is by submitting an application for reconsideration of parking target every year.   Keywords: Retribution Collection for Parking, Regional Government Regulation, Binjai